Prevalence and determinants of depression, anxiety, and burnout among Egyptian house officers during the COVID-19 pandemic - Asmaa Sayed; Marwa Ahmed; Inas El Sayed; Saeed Soliman; Karim Ali; Saged Elsherbiney; Alaaelrahman Shahib; Samar Fares (Middle East Current Psychiatry, 2023)
Abstract Background The COVID-19 pandemic is an unprecedented international health crisis, which has invoked massive consequence on healthcare workers’ mental health and wellbeing. This study aimed to detect the prevalence of anxiety, depression, and burnout among house officers amid the COVID-19 pandemic in Egypt to assess the effect of this pandemic on their mental health. Results A total of 254 house officers were included in this study, and their responses were analyzed. Anxiety, burnout, and depression were reported among 35%, 32%, and 22% of participants, respectively. Multivariate regression analysis found that higher levels of overall worry were associated with anxiety, but not depression or burnout. Having a good personal protective equipment attitude was a significant predictor of both anxiety and burnout. Participants with depression had a higher likelihood of also having a burnout, but a lower likelihood of having anxiety. Overall worry related to the pandemic, depression, and clinical burnout status were all significantly associated with anxiety. Conclusions The study found that anxiety, depression, and burnout are highly prevalent among house officers, who are newly graduated medical professionals. These findings suggest the need for specific programs to address the wellbeing of these individuals during the COVID-19 pandemic.